Zaščitna zakonodaja za slovensko jezikovno manjšino v Italiji in občina Rezija - Valentinčič, Dejan (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2015)
Resia is a part of Slovenian ethnic settlement in Italy, yet due to geographical and historical reasons, most of the population has not developed a sense of Slovenian ethnic identity, but rather, only their local one. After 1999 the municipality of Resia was included into three protection acts for Slovenian linguistic minority. Part of the population and the actual municipal government is categorically opposed to that, which has provoked many drastic conflicts in the valley. In this paper, the author presents and analyses the placement of the municipality of Resia into the protection acts for Slovenian minority, reasons for opposing this placement and the problems with the application of the minority protection by the authorities.
Keywords: Italija; Italy; jezikovne manjšine; narodne manjšine; pravna ureditev; pravno varstvo; Resia, Friuli; Rezija; Slovenci; Slovenes